KEDUDUKAN ANAK PEREMPUAN DALAM PEMBAGIAN HARTA WARISAN MENURUT HUKUM ADAT BATAK TOBA DI KABUPATEN SAMOSIR - Minar Meriyanti; Dilla Hariyanti (Constitutum: Jurnal Ilmiah Hukum, 2023)
Batak society adheres to a patrilineal system, namely taking the male lineage, where only male children have the right to inherit, while married daughters are included in their husband's clan, so that the position of men is more prominent than the position of women. The issues discussed are the position of daughters in the distribution of inheritance and the process of dividing inheritance according to Toba Batak customary law in Samosir Regency. This research is normative legal research that is empirical in nature. The results of the research explain that the position of female children in the distribution of inheritance according to the Batak Toba Samosir custom has changed after the Supreme Court Decision Number 03/Yur/Pdt/2018 regarding disputes over inheritance rights in the Karo traditional patrilineal system, namely the acceptance of female children as heirs like male children. man. The process of dividing inheritance according to Toba Samosir Batak custom is carried out before the heir dies and after the heir dies.